Prevalence of Linguatula serrata nymphs in cattle in abattoirs in Lima, Peru - Castro, Julia (2015)
Linguatulosis is a zoonosis caused by Linguatula serrata. The nymph and adult stages of the parasite can affect humans, and the man main mechanisms of transmission is through contact with domestic dogs and ingestion of uncooked infected cattle viscera. This study aimed to determine the prevalence, mean abundance, and the mean intensity of the nymphal stage ofL. serrata in mesenteric lymph nodes of cattle slaughtered in two abattoirs in Lima, Peru. The animals were brought from the departments of Puno, Junín, La Libertad, Amazonas, Pasco and Lima. A total of 3576 lymph nodes from 368 cattle were collected, fat was removed and stored at 5 °C. Nodes with micro abscesses, calcified granulomas and yellow, green or gray nodules were selected and longitudinal cuts were done. Nymphs were fixed and mounted for evaluation. Results of the morphometry showed averages of 4.95 mm total length, 1.39 mm anterior width and 0.76 mm posterior width. The prevalence of infection by nymphs ofL. serrata was 5.97%, especially in 4-5 years old animals. The most frequent affected cattle were from Chachapoyas, Amazonas (13/121) and Huancayo, Junín (6/70). The mean abundance was 0.14 (0-2) and the mean intensity was 2.5 (2-3).